The Role of Islamic Religious Education Teachers in Developing Understanding of Religious Moderation Among Adolescents - Aep Saepudin (Global Writing Academica Researching and Publishing, 2021)
The development of an increasingly complex and diverse society demands an understanding of religious moderation among adolescents to avoid the potential for extremism. Islamic Religious Education teachers have a strategic role in developing moderate attitudes through an inclusive and open approach. In this context, it is important to explore the challenges faced by adolescents and the strategies that can be applied in the process of religious learning. This study aims to identify the role of Islamic Religious Education teachers in building an understanding of religious moderation among adolescents. This study uses a qualitative approach with data collection through interviews, observations, and document analysis from various relevant sources. The results of the study indicate that synergy between schools, families, and communities is very important in supporting religious moderation. In addition, open discussion methods and the use of relevant media can increase student involvement in learning. This finding also confirms that support from families and communities can strengthen the values ​​of moderation taught in schools. Thus, good collaboration between various parties is key to forming adolescents who are tolerant and respect differences. This study is expected to contribute to the development of more effective and inclusive religious education.